2016
DOI: 10.5009/gnl15529
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Proton Pump Inhibitor Therapy on Gut Microbiota in F344 Rats: Pilot Study

Abstract: Background/AimsTo evaluate changes in gut microbiota composition following long-term proton pump inhibitor (PPI) treatment.MethodsTwenty-four-week-old F344 rats were fed diets with (n=6) or without (n=5) lansoprazole for 50 weeks. Profiles of luminal microbiota in the terminal ileum were then analyzed. Pyrosequencing of the 16S rRNA gene was performed using an FLX genome sequencer (454 Life Sciences/Roche).ResultsRats treated with lansoprazole showed significantly reduced body weights compared to controls (lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Moreover, PPI treatment results in modifications in the gut microbiota, with an increase in the Firmicutes population associated with a decrease in Bacteroidetes . Similarly, previous studies have revealed important microbiota changes in the terminal ileum with PPI administration, which can be summarized as an increase in Firmicutes ( Lactobacillus or Clostridium ) and/or a decrease in Bacteroidetes [ 34 , 35 ]. Furthermore, alterations in the gut microbiota (a decrease in Akkermansia and Coprococcus and an increase in Bacteroidales ) and weight loss after the administration of omeprazole in C57BL/6 J mice has been reported [ 36 ].…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, PPI treatment results in modifications in the gut microbiota, with an increase in the Firmicutes population associated with a decrease in Bacteroidetes . Similarly, previous studies have revealed important microbiota changes in the terminal ileum with PPI administration, which can be summarized as an increase in Firmicutes ( Lactobacillus or Clostridium ) and/or a decrease in Bacteroidetes [ 34 , 35 ]. Furthermore, alterations in the gut microbiota (a decrease in Akkermansia and Coprococcus and an increase in Bacteroidales ) and weight loss after the administration of omeprazole in C57BL/6 J mice has been reported [ 36 ].…”
Section: Discussionmentioning
confidence: 84%
“…To examine the effects of PPIs in detail, we focused on the analysis of the microbiota in the jejunum. Prior studies have shown that PPI causes dysbiosis, increasing the levels of Lactobacillus and Streptococcus in ileum and fecal samples [27][28][29] while reducing Bifidobacteria levels in fecal samples; 30 we made a similar observation ( Figure S1, Figure 2, Figure S5). In the clinical study as shown in Figure 2a and S1, the relative abundance of Akkermansia was not changed.…”
Section: Discussionsupporting
confidence: 76%
“…[116] In rat models, long-term use of lansoprazole (50 weeks) was associated with significant shift in terminal ileum bacterial composition: a predominance of Proteobacteria (93.9%, mainly Escherichia and Pasteurella genera) in the controls and the abundance of Firmicutes (66.9%, mainly Clostridium and Lactobacillus genera) in the treatment group. [117]…”
Section: Intestinal Microbiomementioning
confidence: 99%